Thermosetting resin for fixing electronic components and its preparation process
By modified fluorine -containing organic matter and silicon -containing groups, and combined with the surface modification of 3D mesh nitride heat patching, it solves the problem of insufficient thermal resin thermal conductivity, realizes thermal conductivity and mechanical performance Coordination improvement.
Patent Information
- Application Number
- CN202411719080.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing thermosetting resins are insufficient in applications for fixing electronic components, and improving crystallization performance will lead to increased melting point, reduced fluidity and changes in mechanical properties of the resin.
Use fluorine -containing organic matter and silicon -containing group to modify the cyanate resin, and use three -dimensional mesh nitride hot -watering fillers as armal inside fillers. Sexuality and combination to promote the crystallization of resin.
It significantly improves the thermal conductivity and mechanical properties of thermosetry resin, and is suitable for areas that require high -efficiency thermal transmission and excellent mechanical properties.
Smart Images

Figure CN119192837B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermosetting resin materials, and in particular to a thermosetting resin for fixing electronic components and a preparation process thereof. Background Art
[0002] Cyanate ester resin is a high-performance thermosetting resin. The cured material has excellent heat resistance. In high temperature environment, cyanate ester resin has very good stability, is not easily affected by moisture or thermal degradation, has extremely low hygroscopicity and good dimensional stability. In addition, this resin also has excellent dielectric properties, and its dielectric constant and dielectric loss remain at a low level over a wide frequency and large temperature range. Due to these excellent properties, cyanate ester resin is often used in the field of electronic packaging. However, cyanate ester resin also has its limitations. Its thermal conductivity is low, which to some extent limits its application in modern electronic products.
[0003] In order to improve its thermal conductivity, a common method is to add thermal conductive fillers such as silicon dioxide, boron nitride, graphene, etc. to cyanate resin. These fillers have higher thermal conductivity and can effectively conduct heat, thereby improving the thermal conductivity of cyanate resin. However, there are the following shortcomings, such as the Chinese patent application with authorization announcement number CN104231624B discloses a modified cyanate resin thermal conductive composite material and a preparation method thereof, using graphene and carbon nanotubes to modify cyanate resin, although there is a certain improvement in thermal conductivity, but graphene and carbon nanotubes are difficult to disperse in the matrix, and graphene and carbon nanotubes are dispersed and distributed, and it is difficult to form a thermal conductive network in cyanate resin, so the thermal conductive effect still has certain limitations. Improving the crystallization performance of cyanate resin can improve its thermal conductivity to a certain extent, but it is also faced with some challenges and limitations. First, improving the crystallization performance may cause the melting point of the resin to increase, increase processing difficulty and cost. Secondly, the improvement of the crystallization performance may reduce the fluidity of the resin and affect the processing process. In addition, the change of mechanical properties is also a consideration. The increase of crystallization performance may increase the rigidity and strength of the resin, but reduce the toughness and impact strength. Finally, improving crystallization performance may increase the shrinkage of the resin, which is difficult for applications with high precision requirements. In view of the above problems, it is necessary to develop a thermosetting resin and its preparation process for electronic component fixation, which has high thermal conductivity to meet the needs of thermosetting resins for electronic component fixation. Summary of the invention
[0004] The purpose of the present invention is to provide a thermosetting resin for fixing electronic components and a preparation process thereof, so as to solve the problem that the thermal conductivity of the current thermosetting resin is insufficient.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The thermosetting resin for fixing electronic components comprises the following components in parts by weight: 50-75 parts of modified cyanate resin, 10-30 parts of surface modified three-dimensional network aluminum nitride thermal conductive filler, and 3-8 parts of curing agent.
[0007] Furthermore, the preparation method of the modified cyanate ester resin is as follows: by weight, 100 parts of bisphenol A cyanate ester resin, 4 to 10 parts of fluorine-containing organic matter, 5 to 12 parts of silicon-containing organic matter and 10 to 20 parts of dimethylformamide are added to a reaction kettle, mixed and stirred at 120 to 160° C. for 2 to 4 hours, and then cooled.
[0008] Furthermore, the fluorine-containing organic compound is hexafluorobisphenol A diacrylate or perfluorostyrene.
[0009] Furthermore, the silicon-containing organic compound is methylphenyl silicone resin or aminosilane.
[0010] Furthermore, the preparation method of the surface modified three-dimensional network aluminum nitride thermal conductive filler is as follows: in parts by weight, 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 5 to 10 parts of γ-glycidyloxypropyltrimethoxysilane, 2 to 5 parts of organic salt and 40 to 60 parts of acetone are added to a reactor in sequence, and then reacted for 2 to 6 hours. During the reaction, acetic acid is used to adjust the pH to 5 to 7, and then the surface modified three-dimensional network aluminum nitride thermal conductive filler is obtained after filtering, washing and drying.
[0011] Furthermore, the organic salt is sodium oxalate or sodium succinate.
[0012] Furthermore, the three-dimensional network aluminum nitride thermal conductive filler is composed of micrometer-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial shape.
[0013] Furthermore, the preparation method of the three-dimensional network aluminum nitride thermal conductive filler is as follows: in parts by weight, 40 to 80 parts of aluminum nitride whiskers, 9 to 18 parts of aluminum oxide powder, 3 to 6 parts of carbon powder and 0.2 to 0.8 parts of nickel nitrate are evenly mixed, and then heat treated at 1200 to 1400° C. for 2 to 6 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.
[0014] Furthermore, the mass ratio of the aluminum oxide powder to the carbon powder is 3:(1-2).
[0015] Furthermore, the curing agent is 2,2'-diallyl bisphenol A or triethylenetetramine.
[0016] The present invention also provides a preparation process of a thermosetting resin for fixing electronic components, comprising:
[0017] According to the weight ratio, the modified cyanate resin and the surface modified three-dimensional mesh aluminum nitride thermal conductive filler are added to the mixer in sequence for stirring at a stirring speed of 150-300 rpm for 60-120 min, and then the curing agent is added to continue to be fully stirred, and then poured into a preheated mold, and then placed in a vacuum defoamer for defoaming treatment, and then placed in a vacuum drying oven for staged curing treatment. The staged curing treatment is first heated and cured at 80°C for 2h, then heated and cured at 120°C for 2h, then heated and cured at 160°C for 2h, then heated and cured at 180°C for 2h, and then heated and cured at 220°C for 2h, and finally treated at 240°C for 2-4h to obtain a thermosetting resin for fixing electronic components.
[0018] The purpose of modifying the cyanate resin by using fluorine-containing organic compounds and silicon-containing groups in the present invention is that in terms of thermal conductivity, these two substances can optimize the molecular structure of the resin, reduce the heat conduction resistance, and thus improve its thermal conductivity, making it more suitable for fields requiring efficient heat conduction such as electronic packaging. In terms of mechanical properties, fluorine-containing organic compounds and silicon-containing groups can enhance the hardness and durability of the cyanate resin, and improve its impact resistance and fatigue resistance.
[0019] The three-dimensional mesh aluminum nitride structure of the thermal conductive filler of the present invention has the following advantages. First, the three-dimensional mesh aluminum nitride structure is composed of micrometer-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires. The aluminum nitride whiskers have a large surface area and heat conduction path, which can effectively conduct heat energy, while the aluminum nitride nanowires have a smaller scale and higher thermal conductivity. By combining the two, an efficient heat conduction channel can be formed in the thermal conductive material to improve the thermal conductivity of the material. In addition, the divergent structure of the aluminum nitride nanowires in the present invention also has advantages. The divergent structure provides more heat conduction paths and channels, which can conduct heat energy more effectively. This structure can increase the contact area between the thermal conductive filler and the matrix material, improve the thermal conduction efficiency, and by in-situ growing aluminum nitride nanowires, the combination between the whiskers and the nanowires can be increased, further improving the thermal conductivity. Finally, the aluminum nitride nanowires are in a divergent mesh to avoid the agglomeration of nanowires. In summary, the three-dimensional network aluminum nitride structure used in the present invention has high thermal conductivity. It is composed of micron-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires, and the combination of the two is increased by in-situ growth. The divergent structure of the aluminum nitride nanowires also has the advantage of providing more thermal conduction paths and channels, further improving thermal conductivity and heat conduction efficiency.
[0020] The present invention is to improve the compatibility and combination between aluminum nitride and cyanate resin by surface modification of thermal conductive filler, respectively using γ-glycidyl ether oxypropyl trimethoxy silane and sodium oxalate or sodium succinate, and promote the crystallization of cyanate resin by sodium oxalate or sodium succinate, so as to achieve the improvement of thermal conductivity and good toughness matching of amorphous and crystalline cyanate resin. Specifically, by the modification treatment of γ-glycidyl ether oxypropyl trimethoxy silane, the compatibility and bonding force of filler and cyanate resin can be increased. The modified surface provides more interaction sites, enhances the adhesion between filler and resin, thereby enhancing the bonding ability between them and improving thermal conductivity. In addition, the introduction of sodium oxalate or sodium succinate can promote the crystallization process of cyanate resin, and sodium oxalate or sodium succinate has a catalytic effect, which can improve the orderly arrangement and crystallization rate of resin molecules, thereby enhancing the crystallization performance of resin. By introducing sodium oxalate or sodium succinate on the surface of the thermally conductive filler, a crystalline cyanate resin can be formed on the surface. This crystalline resin has a fast heat conduction channel, which is beneficial to improving thermal conductivity. At the same time, the crystalline cyanate resin is avoided from being evenly distributed in the matrix, and a good match of strength and toughness is achieved. Therefore, the present invention achieves a synergistic improvement of mechanical properties and thermal conductivity by surface modification of the thermally conductive filler, respectively using γ-glycidyloxypropyltrimethoxysilane and sodium oxalate or sodium succinate. By increasing the compatibility and bonding force of aluminum nitride and cyanate resin, and promoting the crystallization of cyanate resin, the thermally conductive filler can have excellent thermal conductivity and good match of strength and toughness.
[0021] Beneficial Effects
[0022] The present invention uses fluorine-containing organic matter and silicon-containing groups to modify the cyanate resin, aiming to improve its thermal conductivity and mechanical properties, making it more suitable for fields requiring efficient heat conduction. The modification optimizes the molecular structure of the resin, reduces the heat conduction resistance, improves the thermal conductivity, and enhances the hardness, durability, impact resistance and fatigue resistance of the resin. In addition, a three-dimensional mesh aluminum nitride structure is used as a thermal conductive filler, which contains micron-scale aluminum nitride whiskers and nano-scale aluminum nitride nanowires, and the combination between the two is increased by in-situ growth. This special structure provides more thermal conduction paths and channels, further improving the thermal conductivity and thermal conduction efficiency. In addition, by using γ-glycidyloxypropyltrimethoxysilane and sodium oxalate or sodium succinate to modify the surface of the thermal conductive filler, the compatibility and bonding degree between aluminum nitride and cyanate resin can be improved. Sodium oxalate or sodium succinate can also promote the crystallization of cyanate resin, thereby improving thermal conductivity and achieving good strength and toughness matching of amorphous and crystalline cyanate resins. In general, the present invention successfully overcomes the problem of insufficient thermal conductivity and mechanical properties of thermosetting resins in traditional technical solutions by modifying cyanate resins with fluorine-containing organic compounds and silicon-containing groups, and preparing three-dimensional network thermal conductive fillers, and achieves a synergistic improvement in thermal conductivity and mechanical properties. The modified cyanate resin has excellent thermal conductivity and good strength and toughness matching, and is suitable for fields requiring efficient thermal conduction and excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a morphology image of the three-dimensional network aluminum nitride thermal conductive filler prepared in Example 1 of the present invention;
[0024] Figure 2 This is an XRD phase analysis diagram of the three-dimensional network aluminum nitride thermal conductive filler prepared in Example 1 of the present invention;
[0025] Figure 3 This is the XRD phase analysis diagram of the thermosetting resin for fixing electronic components prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0027] In the case of not specifying specific conditions, the operation in the examples is carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. Parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters.
[0028] Table 1 below shows the reagents required for the examples and the corresponding purchasing companies:
[0029] Table 1 Reagents required for the examples and corresponding purchasing companies
[0030]
[0031] Example 1
[0032] Thermosetting resin for fixing electronic components comprises the following components in parts by weight: 50 parts of modified cyanate resin, 10 parts of surface modified three-dimensional network aluminum nitride thermal conductive filler, and 3 parts of curing agent.
[0033] The preparation method of the modified cyanate ester resin is as follows: by weight, 100 parts of bisphenol A cyanate ester resin, 4 parts of fluorine-containing organic matter, 5 parts of silicon-containing organic matter and 10 parts of dimethylformamide are added to a reaction kettle, mixed and stirred at 120° C. for 2 hours, and then cooled.
[0034] The above-mentioned fluorine-containing organic matter is hexafluorobisphenol A diacrylate; the silicon-containing organic matter is methylphenyl silicone resin.
[0035] The preparation method of the above-mentioned surface modified three-dimensional network aluminum nitride thermal conductive filler is as follows: by weight, 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 5 parts of γ-glycidyloxypropyltrimethoxysilane, 2 parts of organic salt and 40 parts of acetone are added to a reactor in sequence, and then reacted for 2 hours. During the reaction, acetic acid is used to adjust the pH to 5, and then the surface modified three-dimensional network aluminum nitride thermal conductive filler is obtained after filtering, washing and drying.
[0036] The above-mentioned organic salt is sodium oxalate.
[0037] The three-dimensional network aluminum nitride thermal conductive filler is composed of micrometer-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial shape.
[0038] The preparation method of the above-mentioned three-dimensional network aluminum nitride thermal conductive filler is as follows: in parts by weight, 40 parts of aluminum nitride whiskers, 9 parts of aluminum oxide powder, 3 parts of carbon powder and 0.2 parts of nickel nitrate are evenly mixed, and then heat treated at 1200°C for 2 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.
[0039] The mass ratio of the above-mentioned aluminum oxide powder to carbon powder is 3:1.
[0040] The above-mentioned curing agent is 2,2'-diallyl bisphenol A.
[0041] The present invention also provides a preparation process of a thermosetting resin for fixing electronic components:
[0042] According to the weight ratio, the modified cyanate resin and the surface modified three-dimensional network aluminum nitride thermal conductive filler are added to the mixer in turn for stirring at a stirring speed of 150 rpm for 60 min, and then the curing agent is added to continue to stir thoroughly and evenly, and then poured into the preheated mold, and then placed in a vacuum defoamer for defoaming treatment, and then placed in a vacuum drying oven for staged curing treatment. The staged curing treatment is first heated and cured at 80°C for 2h, then heated and cured at 120°C for 2h, then heated and cured at 160°C for 2h, then heated and cured at 180°C for 2h, and then heated and cured at 220°C for 2h, and finally treated at 240°C for 2h to obtain a thermosetting resin for fixing electronic components.
[0043] The structural composition and phase characteristics of the prepared three-dimensional network aluminum nitride thermal conductive filler were obtained through scanning electron microscopy (SEM) morphology observation, X-ray diffraction (XRD) phase analysis and other characterization methods: Figure 1 Morphological analysis shows that the three-dimensional network aluminum nitride thermal conductive filler prepared in Example 1 presents a three-dimensional network structure constructed by interweaving micrometer-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires, which provides an excellent structural basis for it to serve as a thermal conductive path. Figure 2 It can be seen from the phase analysis results of the three-dimensional network aluminum nitride thermal conductive filler that it contains only a single phase of aluminum nitride and no other impurities. Figure 3 The thermosetting resin for fixing electronic components prepared in Example 1
[0044] XRD phase analysis diagram of thermal conductive resin. From the XRD spectrum, we can see that in addition to the aluminum nitride phase, it also contains crystalline cyanate ester resin. Its broad peak proves that it is nanocrystalline, proving that the surface modified three-dimensional network aluminum nitride thermal conductive filler can promote the crystallization of cyanate ester resin, thereby improving the mechanical properties and thermal conductivity.
[0045] Example 2
[0046] Thermosetting resin for fixing electronic components comprises the following components in parts by weight: 60 parts of modified cyanate resin, 15 parts of surface modified three-dimensional network aluminum nitride thermal conductive filler, and 4 parts of curing agent.
[0047] The preparation method of the modified cyanate ester resin is as follows: by weight, 100 parts of bisphenol A cyanate ester resin, 5 parts of fluorine-containing organic matter, 6 parts of silicon-containing organic matter and 14 parts of dimethylformamide are added to a reaction kettle, mixed and stirred at 130° C. for 3 hours, and then cooled.
[0048] The above-mentioned fluorine-containing organic compound is perfluorostyrene.
[0049] The above-mentioned silicon-group-containing organic compound is aminosilane.
[0050] The preparation method of the above-mentioned surface modified three-dimensional network aluminum nitride thermal conductive filler is as follows: in parts by weight, 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 6 parts of γ-glycidyloxypropyltrimethoxysilane, 3 parts of organic salt and 45 parts of acetone are added to the reactor in sequence, and then reacted for 4 hours. During the reaction, acetic acid is used to adjust the pH to 5.5, and then the surface modified three-dimensional network aluminum nitride thermal conductive filler is obtained after filtering, washing and drying.
[0051] The above-mentioned organic salt is sodium succinate.
[0052] The three-dimensional network aluminum nitride thermal conductive filler is composed of micrometer-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial shape.
[0053] The preparation method of the above-mentioned three-dimensional network aluminum nitride thermal conductive filler is as follows: in parts by weight, 50 parts of aluminum nitride whiskers, 12 parts of aluminum oxide powder, 4 parts of carbon powder and 0.4 parts of nickel nitrate are evenly mixed, and then heat treated at 1300°C for 4 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.
[0054] The mass ratio of the above-mentioned aluminum oxide powder to carbon powder is 3:1.
[0055] The curing agent is triethylenetetramine.
[0056] The present invention also provides a preparation process of a thermosetting resin for fixing electronic components, which is the same as that in Example 1 and will not be repeated here.
[0057] Example 3
[0058] Thermosetting resin for fixing electronic components comprises the following components in parts by weight: 60 parts of modified cyanate resin, 20 parts of surface modified three-dimensional network aluminum nitride thermal conductive filler, and 5 parts of curing agent.
[0059] The preparation method of the modified cyanate ester resin is as follows: by weight, 100 parts of bisphenol A cyanate ester resin, 8 parts of fluorine-containing organic matter, 10 parts of silicon-containing organic matter and 15 parts of dimethylformamide are added to a reaction kettle, mixed and stirred at 140° C. for 3 hours, and then cooled.
[0060] The above-mentioned fluorine-containing organic compound is perfluorostyrene.
[0061] The above-mentioned silicon-containing organic compound is aminosilane.
[0062] The preparation method of the above-mentioned surface modified three-dimensional network aluminum nitride thermal conductive filler is as follows: in parts by weight, 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 8 parts of γ-glycidyloxypropyltrimethoxysilane, 4 parts of organic salt and 50 parts of acetone are added to the reactor in sequence, and then reacted for 5 hours. During the reaction, acetic acid is used to adjust the pH to 5.5, and then the surface modified three-dimensional network aluminum nitride thermal conductive filler is obtained after filtering, washing and drying.
[0063] The above-mentioned organic salt is sodium succinate.
[0064] The three-dimensional network aluminum nitride thermal conductive filler is composed of micrometer-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial shape.
[0065] The preparation method of the above-mentioned three-dimensional network aluminum nitride thermal conductive filler is as follows: in parts by weight, 70 parts of aluminum nitride whiskers, 15 parts of aluminum oxide powder, 5 parts of carbon powder and 0.6 parts of nickel nitrate are evenly mixed, and then heat treated at 1300°C for 5 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.
[0066] The mass ratio of the above-mentioned aluminum oxide powder to carbon powder is 3:1.
[0067] The curing agent is triethylenetetramine.
[0068] The present invention also provides a preparation process of a thermosetting resin for fixing electronic components, which is the same as that in Example 1 and will not be repeated here.
[0069] Example 4
[0070] Thermosetting resin for fixing electronic components comprises the following components in parts by weight: 75 parts of modified cyanate resin, 30 parts of surface modified three-dimensional network aluminum nitride thermal conductive filler, and 8 parts of curing agent.
[0071] The preparation method of the modified cyanate ester resin is as follows: by weight, 100 parts of bisphenol A cyanate ester resin, 10 parts of fluorine-containing organic matter, 12 parts of silicon-containing organic matter and 20 parts of dimethylformamide are added to a reaction kettle, mixed and stirred at 160° C. for 4 hours, and then cooled.
[0072] The above-mentioned fluorine-containing organic compound is perfluorostyrene.
[0073] The above-mentioned silicon-containing organic compound is aminosilane.
[0074] The preparation method of the above-mentioned surface modified three-dimensional network aluminum nitride thermal conductive filler is as follows: in parts by weight, 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 10 parts of γ-glycidyloxypropyltrimethoxysilane, 5 parts of organic salt and 60 parts of acetone are added to a reactor in sequence, and then reacted for 6 hours. During the reaction, acetic acid is used to adjust the pH to 7, and then the surface modified three-dimensional network aluminum nitride thermal conductive filler is obtained after filtering, washing and drying.
[0075] The above-mentioned organic salt is sodium oxalate or sodium succinate.
[0076] The three-dimensional network aluminum nitride thermal conductive filler is composed of micrometer-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial shape.
[0077] The preparation method of the above-mentioned three-dimensional network aluminum nitride thermal conductive filler is as follows: in parts by weight, 80 parts of aluminum nitride whiskers, 18 parts of aluminum oxide powder, 6 parts of carbon powder and 0.8 parts of nickel nitrate are evenly mixed, and then heat treated at 1400°C for 6 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.
[0078] The mass ratio of the above-mentioned aluminum oxide powder to carbon powder is 3:2.
[0079] The curing agent is triethylenetetramine.
[0080] The present invention also provides a preparation process of a thermosetting resin for fixing electronic components, which is the same as that in Example 1 and will not be repeated here.
[0081] Example 5
[0082] The method is basically the same as Example 1, except that the surface-modified three-dimensional network aluminum nitride thermal conductive filler is 30 parts.
[0083] Comparative Example 1
[0084] The method is basically the same as Example 1, except that the thermosetting resin does not contain the surface-modified three-dimensional network aluminum nitride thermal conductive filler.
[0085] Comparative Example 2
[0086] The method is substantially the same as Example 1, except that the preparation of the modified cyanate ester resin does not include fluorine-containing organic matter.
[0087] Comparative Example 3
[0088] The method is substantially the same as Example 1, except that the preparation of the modified cyanate ester resin does not include organic matter containing a silicon group.
[0089] Comparative Example 4
[0090] It is basically the same as Example 1, except that the three-dimensional network aluminum nitride thermal conductive filler has not been subjected to surface modification treatment.
[0091] Comparative Example 5
[0092] It is basically the same as Example 1, except that the aluminum nitride whiskers and aluminum nitride are added separately in an external manner, so there is no in-situ strong interface bonding between the two, and the two are not connected to form a three-dimensional thermal conductive network.
[0093] Performance Test:
[0094] The peel strength is tested according to IPC-TM-650 method.
[0095] Thermal conductivity is tested according to ASTM-D-5470 method.
[0096] The peel strength and thermal conductivity of the thermosetting resins of Examples 1 to 5 and Comparative Examples 1 to 5 are summarized in Table 2.
[0097] Table 2 Performance test table of thermosetting resins of Example 1 to Example 5 and Comparative Example 1 to Comparative Example 5
[0098]
[0099] The main difference between Example 1 and Comparative Example 1 is whether the thermosetting resin contains a surface-modified three-dimensional network aluminum nitride thermal conductive filler. From Table 2, it can be seen that the surface-modified three-dimensional network aluminum nitride thermal conductive filler can improve the mechanical properties and thermal conductivity of the thermosetting resin.
[0100] The main difference between Example 1 and Comparative Examples 2 and 3 is whether the thermosetting resin uses a modified resin matrix of fluorine-containing organic matter and silicon-containing organic matter. It can be seen that these two can significantly improve the molecular network structure of the resin matrix, which helps to optimize the thermal conductivity and mechanical properties of the thermosetting resin.
[0101] The main difference between Example 1 and Comparative Example 4 is whether the three-dimensional network thermal conductive filler is surface modified. It can be seen that the surface-modified thermal conductive filler can increase its bonding with the matrix resin and promote the crystallization of the nanocrystalline cyanate resin, thereby improving the mechanical properties and thermal conductivity.
[0102] The main difference between Example 1 and Comparative Example 5 is whether the micrometer-scale aluminum nitride is strongly bonded to the interface, and therefore whether the two construct a three-dimensional heat conduction path. From Table 2, it can be seen that the micrometer-scale aluminum nitride whiskers and nanometer-scale nanowires construct a three-dimensional network structure, which can form a fast heat conduction channel and improve mechanical properties.
[0103] In summary, the present invention achieves a synergistic improvement in mechanical properties and thermal conductivity by using a modified resin matrix prepared by using fluorine-containing organic matter and silicon-containing organic matter, as well as a three-dimensional network aluminum nitride thermal conductive filler and a surface modified design thereof, and can significantly improve the mechanical properties and thermal conductivity of thermosetting resins.
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A thermosetting resin for fixing electronic components, characterized in that: The composition comprises the following components in parts by weight: 50-75 parts of modified cyanate resin, 10-30 parts of surface modified three-dimensional network aluminum nitride thermal conductive filler, and 3-8 parts of curing agent; The modified cyanate resin preparation method is as follows: by weight, 100 parts of bisphenol A cyanate resin, 4-10 parts of fluorine-containing organic matter, 5-12 parts of silicon-containing organic matter and 10-20 parts of dimethylformamide are added into a reaction kettle, mixed and stirred at 120-160° C. for 2-4 hours, and cooled; The preparation method of the surface modified three-dimensional network aluminum nitride thermal conductive filler is as follows: by weight, 100 parts of three-dimensional network aluminum nitride thermal conductive filler, 5-10 parts of γ-glycidyloxypropyltrimethoxysilane, 2-5 parts of organic salt and 40-60 parts of acetone are added to a reaction kettle in sequence, and then reacted for 2-6 hours, and acetic acid is used to adjust the pH to 5-7 during the reaction, and then filtered, washed and dried to obtain the surface modified three-dimensional network aluminum nitride thermal conductive filler; The organic salt is sodium oxalate or sodium succinate; The three-dimensional network aluminum nitride thermal conductive filler is composed of micrometer-scale aluminum nitride whiskers and nanometer-scale aluminum nitride nanowires; the aluminum nitride nanowires are in-situ grown on the surface of the aluminum nitride whiskers in a radial shape; The curing agent is 2,2'-diallyl bisphenol A or triethylenetetramine.
2. The thermosetting resin for fixing electronic components according to claim 1, characterized in that: The fluorine-containing organic compound is hexafluorobisphenol A diacrylate or perfluorostyrene.
3. The thermosetting resin for fixing electronic components according to claim 1, characterized in that: The silicon-containing organic matter is methylphenyl silicone resin or aminosilane.
4. The thermosetting resin for fixing electronic components according to claim 1, characterized in that: The preparation method of the three-dimensional network aluminum nitride thermal conductive filler is as follows: by weight, 40 to 80 parts of aluminum nitride whiskers, 9 to 18 parts of aluminum oxide powder, 3 to 6 parts of carbon powder and 0.2 to 0.8 parts of nickel nitrate are evenly mixed, and then heat treated at 1200 to 1400° C. for 2 to 6 hours in a nitrogen atmosphere, and then pickled and dried to obtain a three-dimensional network aluminum nitride thermal conductive filler.
5. The thermosetting resin for fixing electronic components according to claim 4, characterized in that: The mass ratio of alumina powder to carbon powder is 3:(1~2).
6. A process for preparing a thermosetting resin for fixing electronic components, which is used to prepare the thermosetting resin for fixing electronic components according to any one of claims 1 to 5, characterized in that: According to the weight ratio, the modified cyanate resin and the surface modified three-dimensional mesh aluminum nitride thermal conductive filler are added to the mixer in sequence for stirring at a stirring speed of 150-300 rpm for 60-120 min, and then the curing agent is added to continue to be fully stirred, and then poured into a preheated mold, and then placed in a vacuum defoaming machine for defoaming treatment, and then placed in a vacuum drying oven for staged curing treatment. The staged curing treatment is first heated and cured at 80°C for 2h, then heated and cured at 120°C for 2h, then heated and cured at 160°C for 2h, then heated and cured at 180°C for 2h, and then heated and cured at 220°C for 2h, and finally treated at 240°C for 2-4h to obtain a thermosetting resin for fixing electronic components.
Citation Information
Patent Citations
A modified cyanate resin thermally conductive composite material and preparation method thereof
CN104231624B
Organosilane modified bisphenol A cyanate ester resin and preparation method thereof
CN101456953A
Zinc oxide whisker / graphene nanosheet synergistically modified cyanate ester resin heat conduction composite and preparation method thereof
CN104312147A